PETA KENDALI EWMA RESIDUAL PADA DATA BERAUTOKORELASI - DEWIANTARI, NI KADEK YUNI; SUMARJAYA, I WAYAN; GANDHIADI, G.K. (E-Jurnal Matematika; Vol 8 No 1 (2019), 2019)
Control charts with  autocorrelation can be overcome by creating control chart with residuals from the best forecasting model. EWMA control chart is a alternative to the Shewhart control chart when detecting small shifts. The purpose of this study is to make the best forecasting model to obtain residual, and see the stability of the rupiah exchange rate against US dollar using EWMA control chart with residual. The best model of the case is ARIMA (1,1,1). The results of the EWMA residual control chart with ? = 0.1 there is a pattern that makes the process unstable.